The folk arts of Paete status and prospects - Cadang, Jose P. 1923- (1986)
The author presented a descriptive survey of the existing and flourishing folk arts of Paete, Laguna. He attempted to trace the background or origin of each folk art, the role they do for the town's economic progress, the problems they encounter, the possible solutions to such problems, and finally to gather views, opinions, and prospective measures to preserve, improve, perpetuate these folk arts for prosterity.
Vita.
Thesis (M.A.T.)--University of the Philippines, Diliman.
Keywords: Art industries and trade -- Paete; Folk art -- Paete